2007
DOI: 10.1002/hep.22110
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of multiple tumor suppressor genes in aging liver, chronic hepatitis, and hepatocellular carcinoma

Abstract: Aberrant DNA methylation is an important epigenetic alteration in hepatocellular carcinoma (HCC). However, the molecular processes underlying the methylator phenotype and the contribution of hepatitis viruses are poorly understood. The current study is a comprehensive methylation analysis of human liver tissue specimens. A total of 176 liver tissues, including 77 pairs of HCCs and matching noncancerous liver and 22 normal livers, were analyzed for methylation. Methylation of 19 epigenetic markers was quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
236
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(254 citation statements)
references
References 49 publications
14
236
3
1
Order By: Relevance
“…Importantly,hypermethylation of the P0 promoter is sufficient to silence HIC1 expression (28). In line with our methylation results, two studies measured HIC1 promoter hypermethylation in different morphologic grades of the liver and found increasing HIC1 promoter methylation from normal liver tissue, to precancerous liver tissue (showing chronic hepatitis or cirrhosis), to primary hepatocellular carcinoma, but no significant correlation between hypermethylation and HIC1 mRNA expression levels was seen (4,5). These results indicate that mechanisms other than hypermethylation contribute to the low HIC1 expression seen in hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Importantly,hypermethylation of the P0 promoter is sufficient to silence HIC1 expression (28). In line with our methylation results, two studies measured HIC1 promoter hypermethylation in different morphologic grades of the liver and found increasing HIC1 promoter methylation from normal liver tissue, to precancerous liver tissue (showing chronic hepatitis or cirrhosis), to primary hepatocellular carcinoma, but no significant correlation between hypermethylation and HIC1 mRNA expression levels was seen (4,5). These results indicate that mechanisms other than hypermethylation contribute to the low HIC1 expression seen in hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 77%
“…example in primary human hepatocellular carcinomas (4,5). Of note, it was shown that in most cell lines, dense methylation of the HIC1 P0 promoter was sufficient to completely silence HIC1 mRNA expresssion.…”
Section: Hic1 Mrna Is Induced On E2f1 Expression Despite Dense Methylmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, known methylated genes, including SOCS1 and HIC-1, may prove unsuitable for HCC diagnosis due to their high methylation rate in non-tumor liver tissues. 35 In the present study, only SPINT2 showed a complete lack of synchronized methylation trend between HCC and non-tumor tissues, suggesting that it may be highly and more specifically methylated in HCC than the other 6 genes examined in this study. This novel finding obtained from our detailed methylation analysis supports the use of SPINT2 as a molecular marker for HCC.…”
Section: Discussionmentioning
confidence: 43%
“…4 Methylation levels of the promoter CpG islands of six genes in the corpus region of the gastric mucosae according to serum H. pylori antibody titer. Compared to the H. pylori-negative group, the methylation level was consistently increased in a stepwise manner in the low-and high-titer groups (p \ 0.05) viral hepatitis, UC, and H. pylori-related gastritis [32][33][34]. However, attention has rarely been paid to the correlations between the degree of altered DNA methylation and activity of inflammation, probably because of difficulties in quantitatively evaluating inflammation in tissues.…”
Section: Discussionmentioning
confidence: 99%